THE IMPACT OF FRACTAL RENDERING IN MODERN HARDWARE ENVIRONMENTS - Bravo, Arthur da Fonseca; Pinto, Giuliano Scombatti (Revista Interface Tecnológica, 2023)
The calculations and mathematical assumptions that led to the discovery of fractal shapes have been around for a long time. However, it was only in recent decades, with the technological evolution of computers and software, that it became possible to visualize the main fractal shapes that are known today in high resolution, as well as their various applications, both academic and practical. The purpose of this article is to present different methods of rendering a fractal, as well as the fact that each of them has a different impact on modern hardware. The methodology used was bibliographical research. The results showed that the older methods have almost no impact on these environments but still take time to render, unlike more recent methods that require much more computers. Thus, it was possible to conclude that thanks to the better use of GPUs in rendering, forms that previously overloaded even the most modern processors can now be reproduced in simpler environments. Fractal rendering is becoming more and more accessible.